Bacteriology of vaccinated and non-vaccinated eye of cats. - Ismail, Nora; Sabri, Jasni (2010)
Thirty cats were divided into two groups: group 1 (owner-kept cats) and group 2 (stray cats). Group 1 consisted of 11 cats in which the vaccination status was up to date whereas group 2 consisted of 19 cats in which the vaccination status was unknown. Conjunctival swabs were taken from these cats for bacteria isolation and identification. Giemsa staining of the swabs was also conducted to identify Chlamydophila sp. Two cats in group 1, one male and one female Persian which had bilateral watery discharge, were positive (18.18%) for bacteria in their eyes. The male Persian cat was positive for Enterobacter spp. and Moraxella nonliquefaciens bilaterally. However, in both eyes of the female Persian cat, only Enterobacter spp. was isolated. In group 2, 11 domestic short hair stray cats had only Staphylococcus intermedius in their eyes which did not show any ocular discharges. Three cats in this group had bilateral isolation and four had unilateral isolation of this bacteria. Of the 30 cats studied, the most predominant bacteria isolated was S. intermedius (36.67%) followed by Enterobacter spp. (6.6%) and M. nonliquefaciens (3.3%). None of the 30 cats studied showed the presence of Chlamydophila sp. in their eyes and there was no evidence of eye lesions in these cats. It is believed that the S. intermedius isolated was normal conjunctival flora of the eyes of these cats. Enterobacter spp. and M. nonliquefaciens could also be the normal flora of the Persian cats, since these bacteria were isolated from their eyes in the absence of lesions but with ocular discharge that may promote the growth of these microorganisms.